Improving Reading Fluency Through Videoscribe For Student with Learning Disability - Zulmiyetri Zulmiyetri; Kasiyati Kasiyati; Grahita Kusumastuti (Universitas Negeri Padang, 2019)
This study aims to determine the effect of videoscribe for improving reading fluently ability for student with learning disability. This research uses single subject research (SSR) experiment, A-B-A design and data analysis technique using visual graph analysis. The subject of this research is student with learning disability. Target behavior in this study is the speed of reading fluently in short discourse text. Observations were conducted in three sessions. First is baseline session (A1), second, interventions through media videoscribe (B) and last session baseline (A2). Based on the results of research, we knew that the ability of children in reading fluently can be increased through videoscribe. At the baseline condition (A1), the reading fluently ability of the student increases from the duration of four point five minutes to four minutes. In intervention condition (B), the duration becomes shorter in one minute. At the baseline condition (A2) the duration becomes shorter, even without any intervention. Based on data analysis, it can be explained that direction tendency, stability tendency, data trending trend, and level change increase positively, and overlape percentage on inter-condition analysis is 0%. It can be concluded that the media videoscribe can improve reading fluently ability for student with learning disability.